Structure of homeobox-leucine zipper genes suggests a model for the evolution of gene families. - Schena, M (1994)
Homeobox genes are present in both plants and animals. Homeobox-leucine zipper genes, however, have been identified thus far only in the small mustard plant Arabidopsis thaliana. This observation suggests that homeobox-leucine zipper genes evolved after the divergence of plants and animals, perhaps to mediate specific regulatory events. To better understand this gene family, we isolated several sequences containing the homeobox-leucine zipper motif and carried out a comparative analysis of nine homeobox-leucine zipper genes (HAT1, HAT2, HAT3, HAT4, HAT5, HAT7, HAT9, HAT14, and HAT22). Gene structures, sequence comparisons, and chromosomal locations suggest a simple model for the evolution of these genes. The model postulates that a primordial homeobox gene acquired a leucine zipper by exon capture. The nascent homeobox-leucine zipper gene then appears to have undergone a series of gene duplication and chromosomal translocation events, leading to the formation of the HAT gene family. This work has general implications for the evolution of regulatory genes.